A rare vasculitic entity: recurrent cutaneous necrotizing eosinophilic vasculitis - Fan Bai; Wanlong Yu; Yabo Xu; Guoying Miao; Mingjun Lei (Skin Health and Disease, 2026)
Abstract Recurrent cutaneous necrotizing eosinophilic vasculitis (RCNEV) is a rare necrotizing vasculitis limited to the skin. It is diagnosed by characteristic histopathological features. This report presents the cases of two middle-aged men who presented with painful purpura, blisters and ulcers. Autoantibody and antineutrophil cytoplasmic antibody tests were negative, and there was no systemic involvement. Histopathology revealed necrotizing vasculitis of the small dermal vessels with prominent eosinophilic infiltration, confirming the diagnosis of RCNEV. Both patients received moderate-dose glucocorticoids followed by a slow taper, achieving sustained remission without recurrence over a 6-month follow-up period. These two cases enrich the clinicopathological spectrum and underscore the role of cutaneous pathology in diagnosis, allowing us to provide a framework for the management of RCNEV.